(untitled) (JURNAL ADMINISTRASI PUBLIK, 2018)
bstract: Fair compensation and acceptable to employees will encourage employees to work better and affect the quality of public service Manado City Health Office. This study aims to determine and analyse the development of public service quality in Manado City Health Office. Method of taking data in this research using survey by using questionnaire. Data analysis techniques that are simple regression analysis and simple analysis. The result of simple linear regression analysis was assessed by regression coefficient (b) with positive sign that is 0,952 and acquisition of constant value (a) equal to 9,999. Then the equation is Y = 9,999 + 0.952. Based on the results of analysis and Pearson product moment obtained locked coefficient (r) of 0.698 with the coefficient of determination (r2) of 0.488. The result shows that the variable of openness to the quality of public service is equal to 48.8% in accordance with Public Service Quality, which is one of the variables taken by the respondents. By providing fair and reasonable compensation will affect and improve the quality of public services in Manado City Health Office. Keywords: Compensation, Quality of public service